Single-mode Er-doped fiber random laser with distributed Bragg grating feedback - Lizárraga, N.; Puente, N. P.; Chaikina, E. I.; Leskova, T. A.; Méndez, E. R. (Optics express, 2009)
We report the implementation of a one-dimensional random laser based on an Er/Ge co-doped single-mode fiber with randomly spaced Bragg gratings. The random grating array forms a complex cavity with high quality factor resonances in the range of gain wavelengths centered around 1535.5 nm. The reflection spectra of the grating array and the emission spectra of the laser are investigated for different numbers of gratings. The experimental results are compared qualitatively with numerical simulations of the light propagation in one-dimensional Bragg grating arrays based on a transfer matrix method. The system is pumped at 980 nm and the experimentally observed output radiation presents a typical laser threshold behavior as a function of the pump power. We find that the laser output contains several competing spectral modes.